Students’ Perceptions of the Use of Digital Media in English Language Learning at SD Negeri Inpres Kotabaru Nabire - Nabila, Almas Rizkika; Whisnubrata, Antonius Awan Asta Adhiprana; Saboan, Stevani; Kafiar, Imanuel Efata; Irawati, Irawati (Universitas Pattimura, 2026)
This study aims to examine students’ perceptions of the use of digital media in English language learning, particularly in terms of comprehension, attitudes and interest, and student activeness and participation. The study employed a qualitative approach with a descriptive research design. The participants were students of SD Negeri Inpres Kotabaru Nabire selected purposively. Data were collected through observation and interviews. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the use of digital media has a positive impact on English learning. In terms of comprehension, digital media help students understand learning materials more easily, clearly, and contextually, especially in vocabulary and grammar mastery. In terms of attitudes and interest, students show high levels of interest and motivation because learning becomes more engaging and less monotonous. In addition, in terms of activeness and participation, students become more active in classroom learning, participate in digital-based activities, and demonstrate greater learning autonomy. Thus, the use of digital media in English language learning is proven to be effective in improving the quality of learning. This study contributes to the development of more innovative technology-based learning strategies that are aligned with students’ needs in the digital era.